2000
DOI: 10.1034/j.1600-079x.2000.290108.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of oxidatively damaged DNA induced by chromium(III) and H2O2: protection by melatonin and related molecules

Abstract: Chromium (Cr) compounds are known occupational and environmental carcinogens. This trace element is found in the workplace primarily in the valence forms Cr(III) and Cr(VI). Cr(III), which was thought originally to be relatively nontoxic, was recently found to be more reactive toward purified DNA than was chromium(VI). Herein, we examined the ability of Cr(III) to induce oxidative DNA damage by measuring the formation of 8-hydroxydeoxyguanosine (8-OH-dG) in purified calf thymus DNA incubated with CrCl3 plus H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 49 publications
(59 reference statements)
1
75
1
Order By: Relevance
“…Melatonin has been shown to increase the efficiency of the electron transport chain and, as a consequence, to reduce electron leakage and the generation of free radicals (131). It was shown that melatonin reduced the formation of 8-hydroxy-2 -deoxyguanosine, a damaged DNA product, 60 to 70 times more effectively than some classic antioxidants (ascorbate and α-tocopherol) (125). Thus, melatonin acts as a direct scavenger of free radicals and can detoxify both reactive oxygen and reactive nitrogen species and indirectly increase the activity of antioxidative defense systems (129,131,132,156).…”
Section: Effect Of Melatonin On the Longevity Of Fruit Fliesmentioning
confidence: 99%
“…Melatonin has been shown to increase the efficiency of the electron transport chain and, as a consequence, to reduce electron leakage and the generation of free radicals (131). It was shown that melatonin reduced the formation of 8-hydroxy-2 -deoxyguanosine, a damaged DNA product, 60 to 70 times more effectively than some classic antioxidants (ascorbate and α-tocopherol) (125). Thus, melatonin acts as a direct scavenger of free radicals and can detoxify both reactive oxygen and reactive nitrogen species and indirectly increase the activity of antioxidative defense systems (129,131,132,156).…”
Section: Effect Of Melatonin On the Longevity Of Fruit Fliesmentioning
confidence: 99%
“…Many studies have shown that melatonin is highly protective of DNA against oxidative damage. Thus, whether the initial damage to the genome is a consequence of a chemical carcinogen [6,42,75] or to ionizing radiation [44,76], the presence of melatonin greatly attenuates the DNA damage. This protective action is afforded both in vivo as well as in vitro when purified DNA is used.…”
Section: Cancermentioning
confidence: 99%
“…N-acetyl-5-hydroxytryptamine (N-acetylserotonin, NAS) (Fig. 1), the immediate precursor of melatonin, protects against oxidative damage under a variety of experimental conditions [Barsacchi et al, 1998;Qi et al, 2000]. Indole-3-propionic acid (IPA) (Fig.…”
mentioning
confidence: 99%
“…Indole-3-propionic acid (IPA) (Fig. 1), a deamination product of tryptophan, possesses a structure similar to that of melatonin and is a newly discovered free radical scavenger effective in preventing oxidative damage [Chyan et al, 1999;Poeggeler et al, 1999;Qi et al, 2000]. 5-hydroxy-indole-3-acetic acid (5HIAA), the main metabolite of serotonin which is excreted in urine, has been sparingly examined in relation to oxidative stress.…”
mentioning
confidence: 99%